(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2023)
The family is one of the social institutions that suffers most changes over time and the evolution of society, with external and internal changes. These changes significantly affect the State, and consequently the legal norms in force, and the norms that are most affected are those that affect Civil Law and Social Security Law. In this way, the possibility of recognizing social-affective children and multiparenthood is particularly noteworthy, especially with regard to the granting of a pension for death and the possibility of accumulating benefits. For the development of this article, the hypothetical-deductive method was used, through exploratory bibliographic research, through the study of Brazilian legislation and jurisprudence. Thus, this article sought to analyze the possibility or impossibility of accumulating benefits due to the recognition of multiparenthood, analyzing the historical context of the family and its evolution, as well as investigating the jurisprudence and legal gaps for such concession. In view of all the analysis in this article, the possibility of accumulating benefits in case of proven multiparenthood recognition was verified.